Post-reflux swallow-induced peristaltic wave (PSPW): physiology, triggering factors and role in reflux clearance in healthy subjects - Zhang, Mengyu; Yaman, Busra; Roman, Sabine; Savarino, Edoardo; Gyawali, C. Prakash; Gardner, Jerry D.; Sifrim, Daniel (Journal of gastroenterology, 2020)
Background and aims The underlying physiology of post-reflux swallow-induced peristaltic wave (PSPW) is unclear. We aimed to: 1) calculate the probability of a random association between reflux and PSPW; 2) characterize factors that could underlie triggering of PSPW and 3) assess the chemical clearance effect of PSPW in healthy asymptomatic subjects. Methods A total of 251 impedance–pH tracings from healthy asymptomatic subjects were analysed. Twenty consecutive tracings from this pool with 20–40 reflux episodes/24 h and a PSPW index higher than 50% were separately analyzed to evaluate the probability of a random association between reflux and PSPW. The characteristics of reflux episodes followed by a PSPW were compared with those not associated with PSPW. Results A mean time interval of 29.3 s between a reflux episode and the first swallow captured 71% of total reflux episodes, and 67% of accompanying swallows were non-random. Compared to reflux without PSPW, reflux episodes with PSPW were more frequently acidic ( P = 0.048), mixed with gas ( P < 0.0001), of high proximal extent ( P < 0.0001), while awake ( P < 0.0001), and with shorter chemical clearance time ( P = 0.040). High proximal extent, gas presence and occurring while awake were independent factors associated with PSPW ( P < 0.0001). Conclusion Using a time window between reflux and PSPW of around 30 s, the probability of a chance association is around 30%. Reflux episodes with high proximal extent, containing gas and occurring while awake are important factors associated with PSPW in healthy subjects. Reflux episodes with PSPW have a shorter chemical clearance time.